Charge-Coupled Device Based on Optical Tomography System for monitoring multiphase flow - Juliza Jamaludin; Rahim, RA; Rahiman, MHF; Muji, SZM; Rohani, JM; Wahab, YA (Univ Tun Hussein Onn Malaysia, 2024)
Indexed by WOS/Scopus/ERA